Mulheres de Pequim : representações do percurso criativo do espetáculo da Companhia Renascença de Dança - Arce, Carmem Lúcia Meira (2013)
A work of art, to be presented to the public, has in essence the personal brands of the artist who composed it. This creation starts from the relationship between cognitive experiences, body and sensitive man. Dance, in its materiality which is the body and the very scenic choreography, presents signs and symbols that are the impressions choreographer assumptions about a topic, an experience or a fact, and these may influence the way the artist compose his work, thus taking own personal aesthetics. The need to understand this process was the stimulus for this research which proposed to conduct a study on the genetic processes of creation in dance, presenting recurrences of this process and the conversion of the functions of everyday movement for the aesthetic movement. For the analysis we used photographic materials, manuscripts, hemeroteca the choreographer and company director, and videographic material spectacle of dance theater Women in Beijing, Cia Renaissance Dance. These materials, called process documents for Cecilia Salles (1992), are understood as records and traces of the compositional aspects of the artistic work and act as instruments for the reconstruction of choreographic work. This research was made through the cataloging and study of material and symbolic elements that composed the choreography in a cross, multi and interdisciplinary, seeking to reflect on the aesthetic aspects of the act of creation having as theoretical Theory of formativity of Pareyson Luigi (1993), based on the form, content and matter, which constitute the operations of training activities present in human activities that are inseparable from aesthetic experiences, the Iconology, Erwin Panofsky (1991), as the instrument of interpretation and analysis images, and Chevalier and Gheerbrant (2007) as a reference for the meaning of symbols and signs present in the work. These discussions were related to reflections on the language of dance and its relationship to the process of creating the show Women in Beijing. As a result of this study, was presented a storyboard that showed the compositional path of the show from a dance contemporary thought. KEYWORDS: Contemporary Dance, Creation Process, Genetic Criticism.